Status Anak Yang Lahir Dari Kawin Lari Menurut Perspektif Hukum Islam dan Hukum Adat - Lilies Anisah (Fakultas Hukum Universitas IBA Palembang, 2021)
Marriage is the beginning of living together in a bond that is regulated in laws and regulations with the intention of forming a happy family, as mandated by Article 1 of Law Number 1 of 1974 concerning Marriage, which reads: